Diverging trends in the global burden of ischemic heart disease attributable to non-optimal temperatures: a historical analysis (1990–2021) and 2050 projections - Jin, Zehao; Pang, Yuting; Huang, Ziyang; Liu, Jialin; Zhan, Xiaoyi; Wang, Kangwei (Frontiers in Public Health, 2025)
BackgroundThis study aimed to comprehensively evaluate the global burden of temperature-related ischemic heart disease from 1990 to 2021, analyzing the temporal trends and regional disparities stratified by socioeconomic development levels. Furthermore, we identified high-risk populations and mapped the trajectory of disease burden up to 2050 to generate data that will inform the establishment of evidence-based public health interventions and climate adaptation strategies.MethodsA comprehensive analysis was conducted on data derived from the Global Burden of Disease Study 2021 (GBD 2021) to determine the impact of temperature-related ischemic heart disease burden in 204 countries and territories. Primary outcome measures included absolute mortality counts, disability-adjusted life years (DALYs), and age-standardized mortality rates (ASMRs). In addition, temporal trend analysis was conducted using joinpoint regression to identify significant inflection points and calculate the annual percent change (APC) estimates. The future landscape of changes in mortality up to 2050 was predicted using the Bayesian age-period-cohort (BAPC) modeling approach, while accounting for age-specific, period-specific, and birth cohort effects. Socioeconomic stratification was performed using the Sociodemographic Index (SDI) quintiles to compare and characterize the variations in the disease burden across development levels. Data uncertainty was quantified using Monte Carlo simulation methods, and the results were expressed as point estimates and their corresponding 95% uncertainty intervals (UI) to ensure robust statistical inference.ResultsIn 2021, high-temperature exposure contributed to 112,389 IHD deaths globally (95% UI: 17,052-256,434), reflecting a 345.0% increase compared to baseline levels in 1990. The corresponding age-standardized mortality rate increased by 1.34 per 10,000, with an estimated annual percentage change (EAPC) of 1.67 (95% CI: 0.61–2.73). The analysis identified marked sex-specific disparities, characterized by a 41.6% (risk ratio: 1.416, 95% CI not provided) higher mortality risk in males relative to females and a male-to-female DALYs ratio of 1.667. In contrast, low non-optimal temperature was associated with 505,298 IHD deaths globally (95% UI: 432,024-619,922), which represented a 64.4% increase in absolute numbers since 1990 (EAPC: 1.09, 95% CI: 0.77–1.40). In contrast, age-standardized mortality rates decreased by 36.9% annually (EAPC: -2.61, 95% CI: −2.73 to −2.48), indicating improved population-level resilience despite the growing absolute burden. Significant socioeconomic disparities were observed, with low-to-middle SDI regions bearing a disproportionate share (75.0%) of the global high non-optimal temperature-related mortality burden. Geographically, North Africa and the Middle East recorded the highest rates (5.97 per 100,000 population), while high-SDI regions demonstrated a sustained annual decline of 6.8% in age-standardized mortality rates linked to low non-optimal temperature. Analysis of the Bayesian modeling projections for 2050 revealed divergent trajectories: high non-optimal temperature-related age-standardized death rates and DALYs rates are likely to increase by 2.85 per 100,000 and 66.83 per 100,000, respectively. In contrast, age-standardized mortality rates associated with low non-optimal temperature are anticipated to decrease by 6.08 per 100,000, reflecting continued adaptation and improved healthcare infrastructure.ConclusionNon-optimal temperature exposure exerts differential effects on the global IHD mortality burden. Moreover, disease risks linked to high non-optimal temperatures are exacerbated with anthropogenic climate change, which necessitates the formulation of targeted occupational health interventions and enhanced healthcare infrastructure, particularly in low-resource settings. Conversely, while low non-optimal temperature-related mortality risks exhibited a declining age-standardized rates, the growing absolute burden attributable to population aging and persistent energy inequities underscores the need for continued surveillance and intervention. Finally, the disproportionate effect on socioeconomically disadvantaged regions highlights the urgent need for climate-health equity initiatives.